Mineralogical Characterizations of Langkawi Ilmenite Ore for Carbothermal Reduction - A. I. Mohammed; N. F. M. Yunos; M. A. Idris; Z. A. Z. Jamal; N. F. Hayazi; T. Nomura, (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
The mineralogical characterizations of Langkawi’s ilmenite were investigated using XRD, XRF and SEM/EDS for morphological analysis. The minerals mainly consist of the phases of FeTiO3, Fe3O4 and TiO2 by Rietveld refinement, which indicated that the ore contains 35.85% of TiO2 and 26.52% of Fe3O4. The amount of the elements calculated from the quantitative and XRF analysis are reliable and in acceptable ranges. The morphology of the ore shows that the ore is formed mainly in sub-rounded grains with titanium and iron as the main elements. The ore is categorized as a low-grade ore, but it can be upgraded for TiO2 production using carbothermal reduction reactions, where the results of XRD, XRF, SEM showed an extractable amount of TiO2 more than 32wt%.